ARMC5 is part of an RPB1-specific ubiquitin ligase implicated in adrenal hyperplasia. Issue 11 (10th June 2022) - Lao, Linjiang; Bourdeau, Isabelle; Gagliardi, Lucia; He, Xiao; Shi, Wei; Hao, Bingbing; Tan, Minjia; Hu, Yan; Peng, Junzheng; Coulombe, Benoit; Torpy, David J; Scott, Hamish S; et al.
Abstract: ARMC5 is implicated in several pathological conditions, but its function remains unknown. We have previously identified CUL3 and RPB1 (the largest subunit of RNA polymerase II (Pol II) as potential ARMC5-interacting proteins. Here, we show that ARMC5, CUL3 and RBX1 form an active E3 ligase complex specific for RPB1. ARMC5, CUL3, and RBX1 formed an active E3 specific for RPB1. Armc5 deletion caused a significant reduction in RPB1 ubiquitination and an increase in an accumulation of RPB1, and hence an enlarged Pol II pool in normal tissues and organs. The compromised RPB1 degradation did not cause generalized Pol II stalling nor depressed transcription in the adrenal glands but did result in dysregulation of a subset of genes, with most upregulated. We found RPB1 to be highly expressed in the adrenal nodules from patients with primary bilateral macronodular adrenal hyperplasia (PBMAH) harboring germline ARMC5 mutations. Mutant ARMC5 had altered binding with RPB1. In summary, we discovered that wildtype ARMC5 was part of a novel RPB1-specific E3. ARMC5 mutations resulted in an enlarged Pol II pool, which dysregulated a subset of effector genes. Such an enlarged Pol II pool and gene dysregulation was correlated to adrenal hyperplasia in humans and KO mice.